PENGARUH METODE FLIPPED CLASSROOM TERHADAP PEMAHAMAN KONSEP PADA PEMBELAJARAN MATEMATIKA PESERTA DIDIK KELAS V SEKOLAH DASAR - Roni Agus Subagyo; Intan Kumala Dewi; Laikha Listiyani; Budi Murtiyasa; Sumardi, Sumardi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to determine the effect of the flipped classroom learning method on the understanding of mathematical concepts in fifth-grade elementary school students. The research method used is quantitative experimental research employing the Post-Test Only Control Design. The population in this study consists of fifth-grade students at SDN 01 and SDN 02 Pereng, Mojogedang, Karanganyar, with two samples: the control class VA consisting of 10 students and the experimental class VB consisting of 10 students. Data analysis techniques included normality test, homogeneity test, and independent sample t-test with a sig. value (2-tailed) of 0.000 < 0.05. Thus, H0 is rejected, H1 is accepted, and a significant difference is found between the control class and the experimental class. Therefore, it can be concluded that the flipped classroom learning model can enhance the understanding of mathematical concepts for fifth-grade elementary school students.